Quranic narrative approach in character development at CFS IIUM: a post-intervention perception evaluation based on the Theory of Planned Behaviour (TPB) - Mohd Basri, Mohd Rafaei; Mat Russ, Nazirah; Aling, Noor Asiah; Ismail, Nur Farrah Syazwanie; Saidin, Nurhafizah; Mohd Yusof, Muhammad Zahin (Asian Scholars Network, 2025)
In higher education institutions like the Centre for Foundation Studies (CFS), International Islamic University Malaysia (IIUM), character development holds significant importance. However, while character development programs have been flourishing at the CFS with various approaches and nature, there is a need for evaluation and enhancement of these approaches. The Quranic narrative approach at CFS uses Quranic stories to teach moral, ethical, and practical lessons, enriching programs with a holistic perspective that includes both specialized knowledge and broader ethical and societal dimensions in the character development of the students. A notable gap exists in the research regarding the effectiveness of Quranic narratives in character development programs, highlighting the necessity for a comprehensive examination of students' post-intervention perceptions and attitudes. This study aims to bridge this gap by conducting a post-intervention perception evaluation based on the Theory of Planned Behaviour (TPB), assessing the impact of the Quranic narrative approach on character development among CFS IIUM students. Objectives include evaluating the approach's impact, analysing students' post-intervention perceptions, assessing changes in attitudes towards character development, and recommending future intervention improvements. Employing a cross-sectional study design, data is collected post-intervention from 175 respondents across 5 mahallat (residential colleges) at CFS through stratified voluntary sampling procedures. Character development serves as the dependent variable, reflecting changes in students' character traits resulting from Quranic narrative exposure, while the independent variable represents the intervention itself. Findings indicate a positive relationship between the Quranic narrative approach and students' character development. This study contributes to character development literature in educational settings, offering insights into Quranic narrative effectiveness and suggesting avenues for future intervention enhancement.